Review on Energy Effectiveness Methods and Practices Followed in Heritages - Jai Sonker, Dr. Yashwant Singh Rawal (International Journal of Advanced Science and Technology, 2020)
Rajasthan and its cultural diversity incorporating heritage richness had built a global image of some of its districts on the map of global tourism. Cities like Udaipur, Bikaner, Jaipur, Jaisalmer, Jodhpur etc are the main attraction point of world tourism especially for destination wedding and corporate meetings. With the special emphasis over developing the heritage buildings for matching the international standards and other dimensions of hospitality services, energy as one of the significant issues have attracted the attentions of the government, hoteliers, and environment practitioners in the past few years. Since the commercial buildings especially hotels with many functional areas such as guest rooms, laundry, conference halls, restaurant, leisure rooms etc have higher consumption of energy and other resources, so in order to identity the sustainable development of the hospitality sector practicing over energy saving methods and approaching energy efficient practices at all the dimensions which can lead into improved utilization of all the energy parameters become mandatory. For any kind of commercial building minimum energy performance code in India was come into existence in year 2007 as Energy Conservation Building Code (ECBC) and Rajasthan followed the same with some minor improvement in year 2011 as Rajasthan Energy Conservation Building Directives (R-ECBD). An extensive review of the literature was performed to know about several practices and technologies opted by the hotels for energy efficiency that enable performance improvements in energy consumption. This paper is an effort to highlight the major energy conservation practices followed especially in the heritages and the improvements realized under the complex affiliation between the energy efficiency and conservation of heritage richness of the building.